1999
DOI: 10.1007/s00282-999-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

New results in clinical severity of homozygous sickle cell anemia in Dakar, Senegal

Abstract: Despite the unicity of its genetic mutation, Sickle cell homozygosity presents different clinical features. Our objectives were to evaluate disease severity in Senegalese patients. Sixty (60) homozygous sickle cell patients were followed up monthly during one year and disease severity was assessed using the "severity index" (SI) which is resulting from epidemiologic, clinic and biological data. Mean age was 20.13, sex ratio was 0.87 and mean age of diagnosis was 9.8 years. 90% of patients presented vaso-occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 9 publications
6
18
3
4
Order By: Relevance
“…However, since there was only a small number of CAR/CAR haplotypes the associations involving the CAR/CAR genotype with hematological or clinical findings seen in our study and discussed above should be interpreted with caution because some of these associations could be due to chance sampling events. It is interesting to note that we found that the outpatient with the Sen/Atypical haplotype presented low HbF levels and had no history of erythrocyte therapy, possibly suggesting that the Senegal haplotype is associated with mild clinical manifestations, as previously reported by Diop et al (1999).…”
Section: Discussionsupporting
confidence: 64%
“…However, since there was only a small number of CAR/CAR haplotypes the associations involving the CAR/CAR genotype with hematological or clinical findings seen in our study and discussed above should be interpreted with caution because some of these associations could be due to chance sampling events. It is interesting to note that we found that the outpatient with the Sen/Atypical haplotype presented low HbF levels and had no history of erythrocyte therapy, possibly suggesting that the Senegal haplotype is associated with mild clinical manifestations, as previously reported by Diop et al (1999).…”
Section: Discussionsupporting
confidence: 64%
“…In present study mean HbF was 21.91 ± 7.27%, being slightly higher in females as compared to males. These values are consistent with the findings observed by Shrikande AV et al 9 HbF production was genetically determined and Arab-Indian haplotype is associated with higher HbF levels as compared to Cameroon haplotype. This explains the low value of HbF in Nigerian population by Kotila TR et al 4 S Diop et al 10 reported mean age of onset of first symptom in sickle cell anaemia was 9.8 years in Senegal.…”
Section: Discussionsupporting
confidence: 93%
“…Le taux moyen de l'hémoglobine F était de 9,5 ± 8,3%. Des études menées au Sénégal ont montré chez les patients drépanocytaires homozygotes, un taux moyen d'hémoglobine F de 6,8% chez les enfants (Diagne et al, 2000) et de 8,2% chez les adultes (Diop et al, 1999). L'hémoglobine F constitue le principal constituant hémoglobinique durant la période prénatale.…”
Section: Sur Le Plan Biochimiqueunclassified